2007
DOI: 10.1080/10428190601132105
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an association betweenChlamydia psittaciand ocular adnexal lymphoma

Abstract: The objective of this study was to assess whether there is PCR evidence for C. psittaci DNA in ocular adnexal lymphoma specimens collected in an academic institution in the U.S. This was a retrospective, single-center study of patients from 1994 - 2004. We used 28 ocular adnexal lymphoma biopsy specimens from adult patients, 16 control lymphoma specimens from patients with systemic lymphomas not involving the ocular adnexa, and five control benign adnexal tissue samples. The presence of C. psittaci DNA was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Importantly, these findings provide an explanation for the discrepancy between the original study by Ferreri et al (Milan, Italy) and subsequent reports: in Italy, C. psittaci was detected in 87% of ocular adnexal MALT lymphoma 23, while no evidence of infection by this bacterium was demonstrated in cases from the South Florida and Rochester (New York) areas of the USA 25, 26. Such geographical variations are further supported by recent meeting abstracts showing a high prevalence of C. psittaci in ocular adnexal MALT lymphomas from South Korea (26/33) 31, but an absence or a low prevalence in cases from North America (0/15) 32 and Cuba (1/21) 33. Interestingly, such a geographically variable association may also exist within the same country as shown by the differences in the prevalence of C. psittaci in ocular adnexal MALT lymphomas from Italy and the USA observed between the current study and previous reports 23, 25, 26, 32.…”
Section: Discussionmentioning
confidence: 67%
“…Importantly, these findings provide an explanation for the discrepancy between the original study by Ferreri et al (Milan, Italy) and subsequent reports: in Italy, C. psittaci was detected in 87% of ocular adnexal MALT lymphoma 23, while no evidence of infection by this bacterium was demonstrated in cases from the South Florida and Rochester (New York) areas of the USA 25, 26. Such geographical variations are further supported by recent meeting abstracts showing a high prevalence of C. psittaci in ocular adnexal MALT lymphomas from South Korea (26/33) 31, but an absence or a low prevalence in cases from North America (0/15) 32 and Cuba (1/21) 33. Interestingly, such a geographically variable association may also exist within the same country as shown by the differences in the prevalence of C. psittaci in ocular adnexal MALT lymphomas from Italy and the USA observed between the current study and previous reports 23, 25, 26, 32.…”
Section: Discussionmentioning
confidence: 67%
“…While antigen stimulation, which may be directly mediated by surface B-cell receptor and/or indirectly mediated by T cells, is implicated in the pathogenesis of EMZLs in the thyroid, salivary gland and stomach, the etiology of OAEMZL is still controversial. C. psittaci may function as the antigenic stimulus of OAEMZLs in several geographic regions [7], [8], [11], [12]; however, it is not detected in the majority of US patient tumors, in which the antigen is unknown [13], [16], [36]. Overall, there is only scarce published data on the potential role of antigenic stimulation in this lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…1,13,14 Most studies originating from North American institutions did not detect C. psittaci in OAEMZL tumors. 13,15,16 Further, we have previously reported that C. psittaci-negative OAEMZLs usually do not harbor the classical chromosomal translocations t(14;18)(q32;q21) IGH-MALT1 and t(11;18)(q21;q21) API2-MALT1 implicated in the pathogenesis of EMZLs originating in other anatomical locations. 10 The majority of B-cell lymphomas express unique clonal surface B-cell receptors (BCRs) encoded by rearranged heavy (IGHV) and light (IGKV or IGLV) immunoglobulin (Ig) genes that may transmit survival signals following binding to cognate antigens.…”
Section: Introductionmentioning
confidence: 94%